Tricycloalternarene derivatives from the endophytic fungus Guignardia bidwellii PSU-G11 - Ubonta Sommart (2018)
Four new tricycloalternarene derivatives, guignarenones A-D (1-4), along with known (6S,9R)-vomifoliol were isolated from the endophytic fungus Guignardia bidwellii PSU-G11. Their structures were determined on the basis of spectroscopic data. The absolute configurations in 1 were assigned using a combination of the modified Mosher's method and NOEDIFF data. Compound 1 displayed mild cytotoxic activity against oral cavity cancer and African green monkey kidney fibroblast (Vero) cell lines. © 2011 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.